2019
DOI: 10.1111/ctr.13758
|View full text |Cite
|
Sign up to set email alerts
|

Hanging donor lungs give good short‐, mid‐ and long‐term results in lung transplantation

Abstract: Background:Hanging donors are considered as marginal donors and frequently unsuitable for lung transplantation. However, there is no evidence of higher lung transplantation (LTx) morbidity-mortality with lungs providing by hanging donor. Methods:Between January 2010 and July 2015, we performed a retrospective study at Foch hospital. We aimed to assess whether hanging donor grafts are suitable for lung transplantation. Results: A total of 299 LTx were performed. Subjects were allocated to a hanging group (HG) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…While outcomes from donors with severe asthma have been poor (39), a number of more recent reports suggest that donors with other causes of acute airway obstruction can be transplanted. Death from hanging and other causes of acute airway obstruction are thought to cause post-obstructive barotrauma and negative pressure pulmonary edema that historically made these donors poor candidates for transplantation (40). Several studies, however, demonstrated that in otherwise suitable donors, outcomes from these donors are no different than from conventional donors (40,41).…”
Section: Cause Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…While outcomes from donors with severe asthma have been poor (39), a number of more recent reports suggest that donors with other causes of acute airway obstruction can be transplanted. Death from hanging and other causes of acute airway obstruction are thought to cause post-obstructive barotrauma and negative pressure pulmonary edema that historically made these donors poor candidates for transplantation (40). Several studies, however, demonstrated that in otherwise suitable donors, outcomes from these donors are no different than from conventional donors (40,41).…”
Section: Cause Of Deathmentioning
confidence: 99%
“…Death from hanging and other causes of acute airway obstruction are thought to cause post-obstructive barotrauma and negative pressure pulmonary edema that historically made these donors poor candidates for transplantation (40). Several studies, however, demonstrated that in otherwise suitable donors, outcomes from these donors are no different than from conventional donors (40,41). In both studies, these donors represented nearly 10% of all transplants performed at these centers, suggesting wider utilization these donors could have a significant impact on transplant volumes.…”
Section: Cause Of Deathmentioning
confidence: 99%
“…Lung allografts from hanging donors are historically considered marginal. It is believed that post-obstructive barotrauma and injury to alveolar-capillary barrier increases capillary permeability [ 23 , 24 ]. Moreover, when the compression is suddenly removed, a prompt variation in venous return and intrathoracic pressure leads to reperfusion pulmonary edema with hyperemia [ 23 , 24 ].…”
Section: Donor Quality Assessmentmentioning
confidence: 99%
“…It is believed that post-obstructive barotrauma and injury to alveolar-capillary barrier increases capillary permeability [ 23 , 24 ]. Moreover, when the compression is suddenly removed, a prompt variation in venous return and intrathoracic pressure leads to reperfusion pulmonary edema with hyperemia [ 23 , 24 ]. Bennett et al suggested that hanging donors may have higher pulmonary vascular resistance and higher peak airway pressure (PAP) [ 25 ].…”
Section: Donor Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation